PROBABILISTIC SEISMIC HAZARD MAPS OF VIETNAM AND THE EAST VIETNAM SEA - Phuong, Nguyen Hong; Truyen, Pham The (Vietnam Journal of Marine Science and Technology, 2015)
In this paper, the probabilistic seismic hazard maps for the territory of Vietnam and the East Vietnam Sea revised from the existing 2010 ones are presented. An earthquake catalog updated until 2014 and most recent seismotectonic and geodynamic information of South East Asia were used for delineation of 37 seismic source zones in the whole territory of Vietnam and the East Vietnam Sea area extended to 1250E. While the Toro et al. (1997) ground motion prediction equation was used for most seismic sources, the equation developed for the subduction zones by Youngs, Chiou, Silva and Humphrey (1997) was used for the Manila Trench source zone. The hazard maps show distribution of the mean peak ground acceleration (PGA) with 10%, 5%, 2% and 0.5% probability of exceedance in 50 years. The highest hazard areas were revealed in northwestern part of the country, in Dien Bien - Lai Chau and Son La source zones, with the maximum values of PGA for 475 - 9975 years of 180 - 272 gals; and off-shore Vietnam’s South Central coast, in the 1090Meridian Fault source zone, where the maximum values of PGA for 475 - 9975 years are 118 - 285 gals. These PGA maps present both short - term and long - term forecasts of seismic hazard in Vietnam and the East Vietnam Sea and can be used as a reference for antiseismic design and many engineering applications.